Harvesting cover crops for biofuel and livestock production: Another ecosystem service?. (17th May 2020) - Blanco‐Canqui, Humberto; Ruis, Sabrina J.; Proctor, Christopher A.; Creech, Cody F.; Drewnoski, Mary E.; Redfearn, Daren D.
Abstract: Harvesting cover crops (CCs) for livestock and biofuel production can be an important ecosystem service from CCs, but this potential service has not been widely discussed. We reviewed the potential use of CCs for livestock or biofuel production, impacts of CC harvesting on soils and crops, the amount of harvestable CC biomass, and strategies to enhance CC biomass production. We searched literature in Web of Science using terms such as "cover crops, " "harvesting, " "soil properties, " and "crop yield, " among others, and found about 30 papers. The literature indicates that CC harvesting does not generally affect soil properties, crop yields, and weed suppression, although the studies are relatively few. Leaving 7.5‐10 cm of CC stubble after harvest could maintain soil ecosystem services. Cover crops produce 3.37 ± 2.96 Mg ha −1 (mean ± SD) of aboveground biomass and 1.33 ± 0.98 Mg ha −1 of belowground (root) biomass. Root biomass input, representing about 30% of the total CC biomass production, could be critical to the maintenance of soil services after CC harvest. The amount of harvestable biomass while maintaining soil services ranges from 1‐3 Mg ha −1 in semiarid regions and from 1‐6 Mg ha −1 in humid regions for high‐biomass‐producing CCs. Strategies to increase CC biomass production include planting CCs early and terminating late, adapting cropping systems by using earlier‐maturity group varieties, and using flexible cropping systems. Overall, CC harvesting appears feasible, but additional research on CC management and harvesting effects on ecosystem services is needed before harvesting CCs at large scales.